WHY DO ARAB-PALESTINIAN JOURNALISTS DELETE TWEETS? - Zedan, Moatasem; Ringel, Sharon; Davidson, Roei (AoIR Selected Papers of Internet Research, 2023)
In Israel and Palestine, as in many countries, the majority of journalists operate an account on Twitter for different purposes, from news gathering and reporting to attracting new audiences and maintaining a relationship with their readers (Hanusch & Bruns, 2017). Many studies of Twitter’s journalistic role have examined journalists’ tweeting practices and the ways in which Twitter serves as an organizational and individual branding tool (e.g., Molyneux, Holton, & Lewis, 2018). However, only a few studies have examined the patterns of tweet deletion among journalists. Ringel and Davidson (2022) conceptualized the practice of tweet deletion as an instance of “proactive ephemerality, a social media phenomenon that occurs when users intentionally remove their own content from their social media profiles manually or with the aid of mechanical tools” (p. 1218). In this study, we examine the motivations of Arab-Palestinian journalists who operate in Israel for deleting their tweets. Based on semi-structured interviews with Arab-Palestinian journalists working in Israel, we seek to understand why they proactively erase tweets. Further, we wish to consider the implications of such an act for Twitter’s functioning as a public record.